ANALISISnKELAYAKANnOBYEKnWISATA GUA BATU HAPU DI DESA BATU HAPU KECAMATAN HATUNGUN KABUPATEN TAPIN PROVINSInKALIMANTANnSELATAN - Zainal Islami; Khairun Nisa; Asysyifa Asysyifa (Jurnal Sylva Scienteae, 2019)
ABSTRACT.The purpose of this study first to recognize the potential of the landscape cave attractions Batu Hapu with observation at the point where the place has the potential to be doveloped based on the boreau of land management quidelines, both know the potential of the attractions of the cave stone hapu using scores and classification referts to the guidelines on the analysis of the operational areas and natural attraction of the Directorate General of PHKA 2003, the third knows the perception of visitors to the potential that is in the attractions of the stone Hapu the selection of respondents using incitental sampling using tabulations analysis and discussed descriptively. Lanscape assessment results included in criterion A ( high quality) total score 19 with elements that dominate is the form of land and vegetation, assessment of potential tourism potentials for attractiveness (score 870) and accessibility (score 525) including eligible criteria, accomodation (score 105) is not feasible, and skores on the assessment of supporting facilities and infrastucture (score 180) enter criteria eligible. Based on the responses of visitors who come to declare the uniqueness of the attractions found in the cave (46,67%), flora (30%) and fauna (23,33%) and in general visitors who come feel happy and interested visitors to come back.Keywords: landscape; tourism potential; perceptionABSTRAK. Tujuan darinpenelitian ini pertama untuk mengetahui potensi lanskap obyek wisata Gua Batu Hapu dengan pengamatan pada titik tempat-tempat yang mempunyai potensi untuk dikembangkan berdasarkan pedoman penilaian Bureau of Land Management (1986), kedua mengetahui kelayakan potensi obyek wisata Gua Batu Hapu dengan menggunakan skoring dan klasifikasi mengacu pada pedoman analisis daerah operasi dan daya tarik wisata alam Dirjen PHKA 2003, ketiga mengetahui persepsi pengunjung terhadap potensi yang ada di obyek wisata Gua Batu Hapu pemilihan responden menggunkan insidental sampling dengan menggunakan analisis tabulasi dan dibahas secara deskriptif. Hasil penilaian laskap masuk dalam kriteria A (kualitas tinggi) skor total 19 dengan unsur yang mendominasi adalah bentuk lahan dan vegetasi, penilaian kelayakan potensi obyek wisata untuk daya tarik (skor 870) dan aksesibilitas (skor 525) termasuk kriteria layak, akomodasi (skor 105) tidak layak, dan skor penilaian sarana dan prasrana penunjang (skor 180) masuk kriteria layak. Berdasarkan jawaban pengunjung yang datang menyatakan keunikan obyek wisata terdapat pada Gua (46,67%), flora (30%) dan fauna (23,33%) dan secara umum pengujung yang datang merasa senang dan pengunjung tertarik untuk mengunjungi kembali.Kata Kunci: lanskap; potensi obyek wisata; persepsi